Fathering Dynamics and Aggressive Behavior: Uncovering the Impact on Adolescent Criminality - Mira Fauziyya Fatihanna; Annisa Aulia Istiqomah; Sophia Krisabel; Yulina Eva Riany (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The phenomenon of juvenile crime shows a very worrying trend with a significant increase in various types of crimes involving juvenile offenders. The loss of the father's role can lead to problems of anxiety disorders in children, as well as serious charges or even criminal acts in children. The purpose of this study is to identify the influence of father's parenting on the criminal behavior of adolescents who are in LPKA Kelas 1 Tangerang. This research is a quantitative study with a descriptive research design. The population in this study were adolescents andikpas in the Special Development Institute for Children (LPKA) Class 1 Tangerang. The research method used is quantitative with the use of scales as a data collection method. There are three scales used in this study, namely the Parental Acceptance Rejection (PAR-Q) scale, the Adolescent Aggression Questionnaire, and the Juvenile Delinquent Behavior Questionnaire. The results show that the tendency of father's care felt by adolescents LPKA Class I Tangerang is rejection (36.7 percent). Adolescents who are in LPKA Class I Tangerang have an attitude of aggressiveness in behavior towards their environment. Half of the adolescents (53.1) had moderate criminal behavior. These findings can serve as a reference in preventing juvenile delinquency through paternal parenting and adolescent aggression.Fenomena kriminalitas remaja menunjukkan tren yang sangat mengkhawatirkan dengan peningkatan signifikan dalam berbagai jenis kejahatan yang melibatkan pelaku anak usia remaja. Hilangnya peran ayah dapat menimbulkan masalah gangguan kecemasan pada anak, serta kenakan serius atau bahkan tindakan kriminal pada anak. Tujuan penelitian ini adalah mengidentifikasi pengaruh pengasuhan ayah terhadap perilaku kriminal remaja yang berada di LPKA Kelas 1 Tangerang. Populasi dalam penelitian ini adalah remaja andikpas di Lembaga Pembinaan Khusus Anak (LPKA) Kelas 1 Tangerang. Metode penelitian yang digunakan adalah kuantitatif dengan penggunaan skala sebagai metode pengambilan data. Ada tiga skala yang digunakan dalam penelitian ini, yaitu skala Parental Acceptance Rejection (PAR-Q), Adolescent aggression Questionnaire, dan kuesioner perilaku kenakalan remaja. Hasil menunjukkan kecenderungan pengasuhan ayah yang dirasakan oleh remaja andikpas LPKA Kelas I tangerang adalah penolakan (36,7 persen). Remaja yang berada di LPKA Kelas I Tangerang memiliki sikap agresivitas dalam tingkah laku terhadap lingkungannya. Separuh remaja (53,1) memiliki perilaku kriminal yang terkategori sedang. Temuan ini adapat menjadi rujukan dalam mencegah kenakalan remaja melalui pengasuhan ayah dan sikap agresi remaja.